Local tectonic stress regime in the Upper Silesian Coal Basin using primary geodetic data - Szczerbowski, Zbigniew (Geology, Geophysics and Environment, 2025)
Many papers have been devoted to the problematic tectonic stress regime of the Upper Silesian Coal Basin (USCB), particularly relating to the interrelation between the tremors triggered by mining activity and the natural seismicity in the rock mass. This problem is analysed here on the basis of geodetic data in light of the tectonic setting. The author determined the horizontal strain regime in the USCB area with the application of triangular arrays that are formed by a network of GPS/GNSS stations. The primary geodetic data used in this research are the coordinates recorded in time by the stations. They enabled the calculation of the easting and northing components of displacement velocity vector and their errors. 16 permanently installed GPS/GNSS stations are located into the study area and this set led to the construction of 23 different triangles, while the centroid of each triangle was extracted. For each centroid, the deformation parameters were determined: maximal horizontal extension, azimuth of maximal horizontal extension, minimal horizontal extension, maximal shear strain, and area strain. These results were applied to estimate the spatial distributions of the parameters. The distributions reveal that the central part of the study area (the Upper Silesian Trough) is under compression, and is surrounded by extension zones. In general, the distributions of strain estimates correspond to the tectonic pattern of the area. These findings provide a different perspective on former studies on tectonic stress by geological surveys and tectonic influence on seismicity in the USCB area. They confirm earlier assumptions about the occurrence of tectonic stress in the studied area. The determined deformation parameters and their spatial distribution provide an explanation for the occurrence of high-energy tremors in the USCB area.